The Anger of the Main Character in the Perempuan Bersampur Merah Novel by Intan Adaru: A Study of Literary Psychology - Sariban Sariban; Hendrik Furqon; M Ibad Sang Babil; Rahayu Tanti Retno; Choirun Nisa’; Nafa Wahyuningtyas Eka Putri (Edulitics (Education, Literature, and Linguistics) Journal, 2020)
This study aims to describe (1) the form of anger of the main character in the novel "Perempuan Bersampur Merah" by Intan Andaru and (2) the factors of anger of the main character in the novel "Perempuan Bersampur Merah" by Intan Andaru, also describe (3) the psychological impact of the main character in the novel “Perempuan Bersampur Merah” by Intan Andaru. This research is a qualitative descriptive study. The subject of this research is the novel "Perempuan Bersampur Merah" by Intan Andaru. The method of data collection is done by reading and note-taking techniques. The data were analyzed by qualitative descriptive technique, which is a research procedure with descriptive data presented in the form of the author's speech in the novel "Perempuan Bersampur Merah" by Intan Andaru.. The results showed that (1) the form of anger of the main character in the novel "Perempuan Bersampur Merah" by Intan Andaru, namely the anger described by the author in the main character, anger is an expression of human emotions in venting dissatisfaction, disappointment or mistakes when there is an emotional turmoil that does not occur. controlled include revenge, curiosity, irritation, hurt and overflowing emotions (2) the factors of anger between characters in the novel "Perempuan Bersampur Merah" by Intan Andaru there are several factors, namely environmental factors, family factors, social factors. Not only that, anger also arises on the basis of feeling disappointed, irritated, disgusted and annoyed. (3) the psychological impact of the main character in the novel "Perempuan Bersampur Merah" by Intan Andaru caused several problems for the main character, namely being depressed, uncomfortable with their environment, potentially hurting themselves, interfering with children's relationships with parents, even with family, problems with friends peers, school environment, even the environment where the child lives.